A Middle-aged Woman Suffering Buerger’s Disease - M. Aminuddin; Devie Caroline (Cardiovascular and Cardiometabolic Journal, 2020)
A 48 years old woman complains of numbness on her fingers and toes. Her 4th and the 5th right fingertips were painful and then blackened. She had no diabetes and hypertension history. She didn’t smoke, but her husband and son were smokers. On local examination there were necrotic gangrenes on the 4th and the 5th fingertips of the right hand. Laboratory examination results (including immunology marker) were within normal limit. Doppler ultrasound and arteriography showed segmental stenosis and partial occlusion of distal arteries on all extremities. We assessed the patient with Buerger’s disease. The managements were oral analgesic and vasodilator medication. Endoscopic thoracal ganglion sympathectomy was performed, followed by amputation of the necrotic fingers. We did not perform a biopsy, so according to all examinations and also by Shionoya and Olin’s criteria, the patient was more likely to suffer from Buerger’s disease than other peripheral occlusive diseases.